Similarities and differences with the ‘general public’: Chinese civil servants’ attitude to genetically modified organisms and its influencing factors - Zheng Yang; Danfeng Liao; Hepeng Jia (GM Crops & Food, 2023)
ABSTRACTThis study examines Chinese civil servants’ attitudes toward genetically modified organisms by reviewing a national survey of 3,018 Chinese civil servants. The findings show that Chinese civil servants hold a more positive attitude to GMOs than the wider Chinese “general public”, with a similar level of genetic scientific literacy and belief in GMOs conspiracy theories and their influence mechanisms. While the Chinese civil servants’ occupational literacy plays an important role in their GMOs attitude. This study provides a new mind-set for studying some specific groups’ attitudes toward GMOs and related food policies.